Analysis of Hybrid Spectrum Sensing in Cognitive Radio Using Hybrid Approaches - Haribhau Ashok Shinde; Sandeep Garg (Communications)
Cognitive radio (CR) technology enables dynamic spectrum access to meet the growing demand for wireless communication. This study investigates spectrum sensing methods, specifically energy detection (ED) and matched filter detection (MFD), within hybrid strategies. A novel hybrid MFD method was developed and evaluated via MATLAB simulations, analyzing factors like sample size, signal-to-noise ratio (SNR), and false alarm probability. Results reveal that ED has a higher miss-detection rate compared to MFD and the proposed hybrid method, which performs particularly well under low sample counts and SNR conditions. This research enhances spectrum sensing techniques in cognitive radio systems, paving the way for more reliable wireless communication networks.